Cryptic diversity in the Japanese mantis shrimp Oratosquilla oratoria (Crustacea: Squillidae): Allopatric diversification, secondary contact and hybridization - Jiao Cheng (Nature Portfolio, 2017)
Abstract Mounting evidence of cryptic species in the marine realm emphasizes the necessity to thoroughly revise our current perceptions of marine biodiversity and species distributions. Here, we used mitochondrial cytochrome oxidase subunit I (mtDNA COI) and nuclear ribosomal internal transcribed spacer (nrDNA ITS) to investigate cryptic diversity and potential hybridization in the Japanese mantis shrimp Oratosquilla oratoria in the Northwestern (NW) Pacific. Both mitochondrial and nuclear gene genealogies revealed two cryptic species in this morphotaxon, which was further confirmed by extensive population-level analyses. One cryptic species is restricted to cold waters with a distribution range corresponding to temperate affinities, while the other dwelled warm waters influenced by the Kuroshio Current. Their divergence was postulated to be attributable to the vicariant event which resulted from the isolation of the Sea of Japan during the middle Pliocene (c. 3.85 Mya, 95% HPD 2.23–6.07 Mya). Allopatric speciation was maintained by limited genetic exchange due to their habitat preferences. Furthermore, the observation of recombinant nrDNA ITS sequence and intra-individual ITS polymorphism suggested recent hybridization event of the two cryptic species occurred in sympatric areas. Our study also illustrated that the Changjiang River outflow might act as an oceanic barrier to gene flow and promoted allopatric diversification in O. oratoria species complex.